Static tensile test of materials - Toh, Winston Xin Wei (2018)
This Final Year Project (FYP) presents the project B207, Static Tensile Test of materials. In this project, the static tensile test will mainly focus on studying the properties of Aluminium 6061-T6. The results obtain from this experiment would be compared with past findings of pervious FYP students and other related researches. This report will show the data which the student has obtained from the static tensile test, and it will also be compared and analysed with past FYP findings. With this report, readers will be able to use it as a reference for future static tensile tests on Aluminium 6061-T6. Static tensile test is a fundamental test used to determine material’s mechanical properties such as ultimate tensile strength, yield strength, etc. In this FYP, Shimadzu AGX plus 10kn and extensometer would be used to carry out the static tensile test. From the test results, the student would then be able to plot the stress-strain curve of Aluminium 6061-T6 and thus analyse the properties of the tested material. The objective of this project is to study the repeatability of the experiment by fabricating the test specimen and following the procedure according to the ASTM standard, ASTM E8/E8M-16a. Since the properties of materials differ with the different speeds of testing, it is important to have a test standard, such as ASTM, as a benchmark. For this experiment, feed rates of 1.6mm/min, 1.0mm/min and 0.5mm/min will be used for testing. The project will also focus on improving the experiment to obtain more accurate and reliable results. Recommendations for static tensile test will be discussed for future students to make improvement on the experiment. A simple guide will be made by the author at the end of the FYP to provide and assist future student with this project.